Erika Lorenz, Rubén Darío: "Bajo el divino imperio de la música". Ediciones de la Academia Nicaragüense de la Lengua, Managua, 1960. - Gicovate, Bernardo (El Colegio de México, 1966)
Se reseñó el libro: Rubén Darío: "Bajo el divino imperio de la música".